Journey to the Orange Islands ; Secret of the Pink Pokemon - West, Tracey, 1965- (New York, NY : Scholastic Inc., 2021)
Professor Oak sends Ash on a mission to the Orange Islands, where surprises await the young Pokemon trainer at every turn.
The Orange Islands are weird! Ash and the gang discover Pokemon they've never seen before. Onix is made of crystal. Rhyhorn has turned pink. Marill has super sonar. And Snorlax is on a feeding frenzy! There is one thing Ash can count on. Team Rocket is setting their usual traps to swipe rare Pokemon -- and Pikachu, of course. Can Ash stop them before Pikachu becomes Pink-achu?
Texts bound back-to-back and inverted.
Accelerated Reader AR
Keywords: v; Animals, Mythical -- Juvenile fiction; Friendship -- Juvenile fiction; Upside-down books